Biovalorization of Astragalus membranaceus var. mongholicus Stems by White Rot Fungi Under Solid-State Fermentation as Ruminant Feed - Yu-Qiong Wang; Li-Long Luo; Li-Ming Chen; Chang-Long Gou (Agronomy)
The value-added effect of white rot fungi on the feed of Astragalus membranaceus var. mongholicus (AMM) stems was explored. All four types of white rot fungi (Lentinus sajor-caju, Pleurotus ostreatus, Lentinula edodes, and Phanerodontia chrysosporium) reduced the lignocellulose content in AMM stems, improved in vitro dry matter digestibility (IVDMD), and influenced the activity of lignocellulose-degrading enzymes. Lentinus sajor-caju and Phanerodontia chrysosporium exhibited superior effects on lignin degradation and IVDMD and significantly altered non-volatile metabolites and antioxidant capacity. Lentinus sajor-caju fermentation resulted in the strongest antioxidant activity compared to that in the other fungal treatments. The fold change (FC) ratio (>100) of sakuranetin, 2′,6′-Di-O-acetylononin, isoformononetin, and artocarpin was compared between Lentinus sajor-caju and Phanerodontia chrysosporium. Among the phenolic compounds, flavonoids play a key role in antioxidant activity, with 5,6-Dihydroxy-7-methoxyflavone showing a strong correlation with antioxidant activity. This study provides valuable insights for utilizing AMM stem waste in the context of traditional Chinese medicine.